Resiliência psicológica de estudantes da Universidade Federal do Ceará - Chaves, Flora Lima (2019)
The approximation of the complaints of suffering and psychic sickness of the student population of the Federal University of Ceará (UFC) awakens to the necessary investigation of the psychological resources of coping and overcoming adversities and for the analysis of factors related to psychological resilience (self-perception , planned future, social competence, structured style, family cohesion and social resources). In this research, the overall objective was to investigate the psychological resilience factors of UFC students. The research method was quantitative, descriptive and field study. The population was students of the undergraduate courses of UFC Fortaleza. The sample, defined according to accessibility and statistical criteria, was 446 students, of which 254 were from the Center of Sciences (CC) and 192 from the Institute of Culture and Art (ICA). The data collection instrument was a questionnaire structured with objective questions, based on the RSA. Data analysis used classic statistical methods: exploratory data analysis and statistical inference. It was concluded that the means of resilience factors tended to value 4 (four), indicating a balance between risk and protection factors. There were statistically significant differences in the means of the following factors: "self-perception", in the variables "gender", "gender", "sexual orientation" and "age", with superiority of men, males, heterosexuals and of adults (30 to 59 years), respectively; "Planned future", in the variables "sexual orientation" and "age", with superiority of the scores of heterosexuals and adults; "Social competence" in the variables "sexual orientation" and "academic unit", with superiority of the means of the homosexuals and the students of the ICA, respectively; "Structured style", in the variable "sexual orientation", with the superiority of the homosexuals; "Family cohesion", in the variable "sexual orientation", the highest scores being those of heterosexuals. There was statistically significant difference in the final means of the RSA in the variables "sexual orientation" and "age", with superiority of the scores of heterosexuals and adults, respectively. There were no statistically significant differences in the variables "monthly family income" and "student benefit / benefit". Possible strategies for strengthening psychological resilience are suggested based on the observed results, such as the construction of a "Psychological Resilience Development Plan for UFC students", with the participation of faculty, students and technical-administrative servers. having as transversal axes the valorization of the culture of the mutual support, the recognition of potentialities and the stimulus of the cooperation; the instrumentalization of students in the management of their own time; the training of coping strategies and the increase of activities aimed at strengthening students' social skills, such as psychoeducation groups, sports practices and artistic expression.